2017
DOI: 10.3389/fnagi.2017.00259
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent Altered Functional Connections of Default Mode Network in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder associated with the progressive dysfunction of cognitive ability. Previous research has indicated that the default mode network (DMN) is closely related to cognition and is impaired in Alzheimer’s disease. Because recent studies have shown that different frequency bands represent specific physiological functions, DMN functional connectivity studies of the different frequency bands based on resting state fMRI (RS-fMRI) data may provide new insight into AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Royall et al (10) found that DMN atrophy was closely associated with the severity of cognitive impairment in patients with AD. Li et al (11) found that the disruption of DMN was frequency dependent. Banks et al (12) found that left lateralization of DMN was associated with an improvement in recall performance in patients with AD.…”
Section: Introductionmentioning
confidence: 99%
“…Royall et al (10) found that DMN atrophy was closely associated with the severity of cognitive impairment in patients with AD. Li et al (11) found that the disruption of DMN was frequency dependent. Banks et al (12) found that left lateralization of DMN was associated with an improvement in recall performance in patients with AD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have employed connectivity metrics have had initial successes in identifying AD biomarkers, with some reporting specific functional connectivity changes as the disease progresses. To date, multiple studies have reported RSN disturbances in patients with AD, MCI, presymptomatic autosomal dominant AD mutation carriers, and cognitively normal individuals carrying the APOE ε4 risk allele (Agosta et al, 2012;Badhwar et al, 2017;Dillen et al, 2017;Li et al, 2017;Lopez-Sanz et al, 2017;Nakamura et al, 2017;Schumacher et al, 2018). Our study expands upon these earlier reports by using a twopronged network analysis strategy aiming to more fully characterize FC modular organization, and by testing the robustness of our findings across two independent cohorts of participants.…”
Section: Discussionmentioning
confidence: 61%
“…Taken together, our results are consistent with previous studies, suggesting that the cognitive deficits observed in JME may be related to the observed decreased intra-RSN dynamics. More importantly, the between-group differences in intra-RSN dynamics varied across different frequency bands, suggesting the frequency-dependent alteration that the altered FC within RSNs might be tailored to specific frequency bands ( 48 , 49 ). In the present study, we extended current research to temporal dynamic domain and found that the abnormal dynamic FC within RSNs of JME might also be dominated by specific frequency bands.…”
Section: Discussionmentioning
confidence: 99%